The association between perceived cause of glaucoma and illness perceptions - Choe, Eunice; Poleon, Shervonne; Thomas, Tracy; Racette, Lyne (Frontiers in Medicine, 2024)
The perceived cause of disease is an important factor that has been linked with treatment outcomes but has not been fully assessed in primary open-angle glaucoma (POAG). This study assessed the accuracy of patients' perceived cause of POAG and identified associations between accuracy, illness perceptions, medication adherence, and quality of life (QoL).The Brief Illness Perception Questionnaire (BIPQ) was used to assess illness perceptions and asked patients to rank the three most important causes of their disease in order of importance. POAG risk factors recognized by the American Academy of Ophthalmology were used to code responses as accurate or inaccurate based on the following three methods: 1) coding any reported cause, regardless of rank, 2) coding only the first-ranked cause, and 3) coding and weighting all reported causes. Medication adherence was measured electronically. QoL was measured using the Glaucoma Quality of Life questionnaire. Mann-Whitney U test was used to detect differences in illness perceptions, medication adherence, and QoL between accuracy groups.Results: A total of 97 patients identified a cause of their POAG and were included in this analysis. A higher proportion of patients reported an accurate cause (86.6% using method 1, 78.4% using method 2, and 79.4% using method 3; all p < 0.001). Mean medication adherence was 86.0% ± 17.8 and was similar between accuracy groups (all p > 0.05). Using method 2 (p = 0.045) and method 3 (p = 0.028), patients who reported an accurate cause of their POAG believed that their illness would last for a longer time compared to patients who reported an inaccurate cause. Method 3 also revealed that patients who reported an accurate cause of their POAG had lower perceived understanding of their illness (p = 0.048) compared to patients who reported an inaccurate cause. There were no differences in QoL between accuracy groups (all p > 0.05).This study highlights the association between perceived cause of POAG and illness perceptions related to knowledge level and POAG duration. Future studies should assess associations between perceived cause of disease and other critical dimensions of illness perception.